(untitled) (REMUNOM, 2025)
This study aims to describe the development and validation process of a software for the automation of technological management processes in municipal public service. The software seeks to overcome operational bottlenecks in the management of IT assets, promoting efficiency, traceability and transparency through equipment management, loan control and technical support. This initiative aligns with the digital modernization of public administration, adopting data-based solutions to optimize resources and institutional decisions, in addition to fostering sustainable governance and innovation in administrative routines. The methodology adopted a sequential approach in four integrated stages: Design, with scientific prospection in CAPES Periodicals and Google Acadêmico, and technological prospection in SPB and INPI; Requirements Specification, in which functional and non-functional requirements were identified; Development, encompassing Entity-Relationship (MER) modeling and incremental coding in the Laravel framework (MVC standard); Validation, through acceptance tests with 12 professionals, using a 5-point Likert scale. The results highlight the success of the validation, with averages above 4.17 in all statements evaluating usability, intuitiveness and process optimization, with no records of disagreement in seven of the nine questions. The demographic analysis reveals a qualified and diversified sample, generating positive feedback for refinements. This high acceptance confirms the software’s adequacy to real needs, contributing to sustainable administrative efficiency and innovation in the management of IT assets.